Determinant of Tax Payer Compliance in KPP Pratama Makassar Utara - Anthony Holly; Maouren Angel Soewandi; Lukman Tuwo (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2019)
This research aims to determine (1) the influence of Modernization tax administration system on taxpayer compliance in the KPP Pratama Makassar Utara, (2) the influence of tax knowledge on taxpayer compliance in the KPP Pratama Makassar Utara. The research data obtained from questionnaire were distributed to taxpayer in the KPP Pratama Makassar Utara. The sample determined by using purposive sampling with a sample size of 97 respondents. Further data have been obtained, tested by using multiple linear regression analysis. The results of hypothesis test prove that modernization tax administration system has positive impact on the taxpayer compliance and tax knowledge has positive impact on the taxpayer compliance.